2020
DOI: 10.1093/jxb/eraa201
|View full text |Cite
|
Sign up to set email alerts
|

Root phenotypes of young wheat plants grown in controlled environments show inconsistent correlation with mature root traits in the field

Abstract: Using a field to lab approach, mature deep-rooting traits in wheat were correlated to root phenotypes measured on young plants from controlled conditions. Mature deep-rooting root traits of 20 wheat genotypes at maturity were established via coring in three field trials across 2 years. Field traits were correlated to phenotypes expressed by the 20 genotypes after growth in four commonly used lab screens: (i) soil tubes for root emergence, elongation, length, and branching at four ages to 34 days after sowing (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 31 publications
3
56
0
Order By: Relevance
“…Moreover, the opaque nature of the soil further increases the complexity of in‐situ phenotyping of root systems. While controlled (i.e., hydroponic) root phenotyping was not always a good predictor of the field situation (Rich, Christopher, Richards, & Watt, 2020), Alahmad et al (2019) showed that root angle phenotyping in the lab was consistent with the expression in the field. Likewise, seminal root number phenotypes observed in hydroponic conditions are transferrable to soil conditions, especially during the vegetative phase (Golan et al, 2018; Richard et al, 2015; Watt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the opaque nature of the soil further increases the complexity of in‐situ phenotyping of root systems. While controlled (i.e., hydroponic) root phenotyping was not always a good predictor of the field situation (Rich, Christopher, Richards, & Watt, 2020), Alahmad et al (2019) showed that root angle phenotyping in the lab was consistent with the expression in the field. Likewise, seminal root number phenotypes observed in hydroponic conditions are transferrable to soil conditions, especially during the vegetative phase (Golan et al, 2018; Richard et al, 2015; Watt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the opaque nature of the soil further increases the complexity of in-situ phenotyping of root systems. While controlled (i.e., hydroponic) root phenotyping was not always a good predictor of the field situation (Rich, Christopher, Richards, & Watt, 2020), Alahmad et al (2019) showed that root angle phenotyping in the lab was consistent with the expression in the field.…”
Section: Form Lab-to Field-based High-throughput Root Traits Phenotypingmentioning
confidence: 97%
“…Another limitation of the GrowScreen-PaGe is that this environment differs greatly from the one that plants and bacteria would be exposed to in the field. Although previous studies validating lab screens in agricultural fields have shown that germination-paper root screens robustly represent the root architecture of wheat grown in the field at the seedling stage (Rich et al 2020;Watt et al 2013), we are aware that the findings of our study need to be further validated in more realistic conditions. A great challenge for applying the results of bacteria-plant interaction studies to the agricultural sector is the transition from lab experiments (relatively small scale, controlled conditions, one or few stresses applied at the time) to "real" agricultural conditions, characterized by the presence of diverse microbiota in soils, constantly fluctuating growing conditions and multiple biotic interactions in both plants and PGP bacteria.…”
Section: Axile and Branch Roots Were Differentially Affected By Bacterial Inoculationmentioning
confidence: 93%
“…Controlled environment phenotyping is currently a preferred option to field phenotyping because of the ability to control variability and increase repeatability and heritability (Watt et al, 2020). The phenotypes of young wheat plants such as seminal root length and total root length measured in control environments correlate well to expression in fields of those phenotypes (Watt et al, 2013(Watt et al, , 2020Rich et al, 2020). Direct root phenotyping in the field is difficult mainly due to the opaque nature of soil, and is restricted to coring, shovelomics and minirhizotrons, which only reveal part of root systems (Tracy et al, 2019;Wasson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%